A layered computer-interpretable guideline model for easing the update of locally adapted clinical guidelines. (March 2020) - Fux, Adi; Soffer, Pnina; Peleg, Mor
Maintenance of computer-interpretable guidelines is complicated by evolving medical knowledge and by the requirement to customize content to local practice settings. We developed a framework to support knowledge engineers in customization and maintenance of computer-interpretable guidelines specified in the PROforma formalism. In our layered approach, the computer-interpretable guidelines containing the original clinical guideline serves as the primary layer and local customizations form secondary layers that adhere to its schema while augmenting it. Java code unifies the layers into a single enactable computer-interpretable guidelines. We performed a pilot experiment to verify the effectiveness of a layered framework. In this first attempt, we evaluated the hypothesis that the layered computer-interpretable guidelines framework supports knowledge engineers in maintenance of customized computer-interpretable guidelines. Participants who used the layered framework completed an update process of the primary knowledge in less time and made fewer errors as compared to those using the single-layer framework.